LEXICAL AND STYLISTIC MEANS OF FORMING THE POLITICAL IMAGE OF UKRAINE IN PERSIAN MEDIA DISCOURSE - Мазепова, Олена; Петрук, Вероніка (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d. Given the large-scale challenges that our country has faced since the beginning of the full-scale invasion of Russian troops, the study of the verbal representation of the political image of Ukraine in the media of different countries is of particular relevance. Considering the role of Iran as a strategic partner of the aggressor state, we set the goal of identifying what lexical and stylistic means the media use to form the political image of Ukraine in the modern Persian-speaking media space. M e t h o d s. In addition to general scientific methods of analysis and synthesis, we used the observation method (to analyze changes and trends in the use of linguistic means to create the image of Ukraine in the collected corpus of texts), lexical and stylistic analysis (to determine linguistic means that form the image of Ukraine); contextual analysis (to study the contexts in which Ukraine is most often mentioned). R e s u l t s. The study identified three main thematic blocks that determine the political image of Ukraine in modern Persian media discourse. According to the analysis, the positive image of Ukraine is formed by media resources located in Western countries, while the negative image is created by the official Iranian media, which, relying on Russian news agencies, broadcast the corresponding narratives. The analysis of stylistic resources for creating the image of Ukraine showed that epithet is the most frequent of them; metaphor and hyperbole are also actively used, as opposed to simile. C o n c l u s i o n s. The data obtained indicate that the Persian media discourse represents a complex and ambiguous political image of Ukraine, reflecting various aspects of the country's internal political processes and the current geopolitical situation in the world. Positive narratives contribute to the formation of the image of Ukraine as a democratic and responsible international actor, while negative messages bring to the fore issues of Ukraine's dependence on support from Western countries, problems with mobilization and corruption, etc.

В с т у п. З огляду на масштабні виклики, що постали перед нашою країною з початком повномасштабного вторгнення російських військ, дослідження вербальної репрезентації політичного образу України в ЗМІ різних країн набуває особливої актуальності. Враховуючи роль Ірану як стратегічного партнера держави-агресора, ми поставили за мету виявити, які лексико-семантичні та стилістичні засоби використовуються ЗМІ для формування політичного образу України у перськомовному медіадискурсі. М е т о д и. Крім загальнонаукових методів аналізу і синтезу, для досягнення поставленої мети використовувалися: метод спостереження (для аналізу змін та тенденцій у використанні мовних засобів для створення образу України у зібраному корпусі текстів), лексико-стилістичний аналіз (для визначення мовних засобів, що формують образ України); контекстуальний аналіз (для вивчення контекстів, в яких найчастіше згадується Україна). Р е з у л ь т а т и. У ході дослідження було виявлено три основні тематичні блоки, які визначають політичний образ України у перськомовному медіадискурсі. За результатами аналізу, позитивний імідж України формується медіа-ресурсами, дислокованими в країнах Заходу, тоді як негативний образ створюється офіційними ЗМІ Ірану, які спираючись на російські інформагенства, транслюють відповідні наративи. Аналіз стилістичних засобів створення образу України засвідчив, що найчастотнішим із них є епітет; активно вживаються метафора і гіпербола, значно меншою мірою – порівняння. В и с н о в к и. Отримані дані свідчать, що перськомовний медіадискурс репрезентує складний і неоднозначний політичний образ України, що відображає різні аспекти внутрішньополітичних процесів у країні та геополітичної ситуації у світі. Позитивні наративи сприяють формуванню образу України як демократичного і відповідального міжнародного актора, тоді як негативні меседжі виносять на перший план питання залежності України від підтримки західних країн, проблеми з мобілізацією, корупцією тощо.
ЛЕКСИКО-СТИЛІСТИЧНІ ЗАСОБИ ФОРМУВАННЯ ПОЛІТИЧНОГО ОБРАЗУ УКРАЇНИ В ПЕРСЬКОМОВНОМУ МЕДІАДИСКУРСІ
Keywords: the Persian language; Persian media discourse; political image; Russian-Ukrainian war; Ukraine; the Persian language; Persian media discourse; political image; Russian-Ukrainian war; Ukraine; перська мова; перськомовний медіадискурс; політичний імідж; російсько-українська війна; Україна; перська мова; перськомовний медіадискурс; політичний імідж; російсько-українська війна; Україна.